STUDENTS’ PERCEPTION TOWARDS THE USE OF GOOGLE CLASSROOM FOR MATHEMATICS ONLINE LEARNING VIEWED FROM STUDENTS’ READINESS - Pradipta Annurwanda; Rahmat Winata (KALAMATIKA Jurnal Pendidikan Matematika, 2021)
Google Classroom is an online learning app that can be used for free and offers many features to support the online learning system and the implementation of Google Classroom must consider the students' readiness in accessing Google Classroom because many students have difficulty in the learning process, which affects the decline in student assignments and exam scores. The purpose of this study was to describe students’ perception towards the use of Google Classroom in mathematics learning in terms of students' readiness to take online learning. This study was conducted using a survey on 91 mathematics education students of STKIP Pamane Talino. The instrument used in this study was a questionnaire. The survey results showed that the level of readiness of students was 74.60% in the very good category. The effectiveness of Google Classroom implementation on online learning was 71.24% (very good); the use of Google Classroom is effective in learning mathematics in terms of students’ readiness for online learning. The results also show that students can access Google Classroom online to ask the tutors, work on assignments and view the answers to their assignments independently and regularly. Students find learning using Google Classroom is effective and fun because students can study material, discuss with teachers, and send assignments remotely.